EFL Students’ Perceptions of ChatGPT-Assisted Writing: A Qualitative Study of Idea Generation, Language Support, Confidence, and Critical Use - Anna Mariani (Yayasan Pustaka Karya Mandiri, 2026)
The emergence of generative artificial intelligence has transformed how English as a Foreign Language (EFL) students approach writing tasks. ChatGPT is increasingly used by students to generate ideas, organize outlines, improve grammar and vocabulary, revise drafts, and reduce writing anxiety. However, the use of ChatGPT in EFL writing also raises concerns related to accuracy, overreliance, originality, and students’ ability to critically evaluate AI-generated output. This study explores EFL students’ perceptions of ChatGPT-assisted writing. The study employed a qualitative descriptive design involving 30 EFL students. Data were collected through semi-structured interviews consisting of ten questions related to students’ experiences using ChatGPT for writing tasks, idea generation, grammar and vocabulary development, writing confidence, perceived advantages, difficulties, writing enjoyment, verification behavior, recommendation, and suggestions for improving AI-assisted writing. The data were analyzed using thematic analysis by identifying repeated patterns across students’ responses. The findings revealed eight major themes: idea generation, vocabulary development, grammar support, writing confidence, writing efficiency, critical evaluation of AI output, dependence concerns, and positive attitude toward ChatGPT. The most dominant theme was positive attitude toward ChatGPT, appearing in 29 of 30 responses, followed by writing efficiency in 28 responses and idea generation in 27 responses. Students perceived ChatGPT as helpful in making writing faster, more organized, less stressful, and more linguistically supported. However, they also recognized the need to verify AI suggestions and avoid overdependence. The study concludes that ChatGPT can support EFL writing when used as a learning assistant rather than a substitute for student thinking. Its educational value depends on students’ critical awareness, teacher guidance, ethical use, and integration with writing instruction.